Hypermobilitet och smärta hos studenter bland sjukgymnaststudenter vid Luleå tekniska universitet - Holmgren, Josefine; Olsson, Malin (2013)
Hypermobility is a condition where the range of movement is greater than normal. In the world population, 4-40 % is considered living with the condition. Women and individuals with a heritage from Asia and Africa are more likely to have a hypermobility. Hypermobility tends to decrease with age. Symptoms such as pain can occur, but the individuals may as likely be free of symptoms. A simple test to diagnose a general hypermobility is Beighton scale test(BST). In order to prevent hypermobility to affect the individual certain procedures can be done for example training and information. To examine the prevalence of general hypermobilty and its correlation with pain in physiotherapist students in Luleå University of Technology. 42 physiotherapist students were examined with BST and answered a pain and activity questionnaire. 19 of 42 students were hypermobile. The answering frequency was 21 %. There were a bigger number of women in the hypermobile group. 16-58 % of the hypermobile population experienced pain in some way. The main prevalence for pain in the hypermobile group was pain in the back, followed by a feeling of tiredness in the back. More research is needed in this area to understand the impact of general hypermobilty and pain, and to closer examine what preventive measures that should be used to avoid future symptoms. The result of this study reflects the current research. Pain seems to be less present in hypermobile individuals who exercise regularly. This is a positive factor for physiotherapists. Validerat; 20130124 (global_studentproject_submitter)